2019
DOI: 10.1002/lary.27770
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐based outcomes in type I thyroplasty for nonparalytic glottic incompetence

Abstract: Objective: Clinical outcomes for type I Gore-Tex thyroplasty (GMT) for nonparalytic glottic incompetence (GI) have been reported in the literature. Given differences in male and female laryngeal anatomy, sex-based outcomes should also be evaluated. We endeavored to evaluate sex-specific post-GMT voice outcomes.Methods: We performed a retrospective review of patients undergoing GMT for nonparalytic GI. Multidimensional voice outcome measures including voice-related quality of life (VRQOL), Glottal Function Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Another previous study reported sex differences for GFI for both UVFP and presbylarynges patients after medialization laryngoplasty, but no previous study has reported significant sex differences for airflow, either pre- or post-treatment for either of these diagnoses. 22 This study demonstrated a significant difference in mean airflow based on sex, with a medium effect size. Across all etiologies and diagnoses, females had significantly lower airflows compared to males (Table 1).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Another previous study reported sex differences for GFI for both UVFP and presbylarynges patients after medialization laryngoplasty, but no previous study has reported significant sex differences for airflow, either pre- or post-treatment for either of these diagnoses. 22 This study demonstrated a significant difference in mean airflow based on sex, with a medium effect size. Across all etiologies and diagnoses, females had significantly lower airflows compared to males (Table 1).…”
Section: Discussionmentioning
confidence: 58%
“…21 Sex-based differences have been found for GFI ratings in UVFP and presbylarynges patients. 22 Differences in s/z ratios have been found with impaired power source for voicing. [23][24][25] Differences in flow, GFI and s/z ratios have already been demonstrated between diagnoses of UVFP, BVFP, and presbylarynges.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, we found a lowered, but still higher than normal fundamental frequency in males after bilateral medialization thyroplasty, both for atrophy and atrophy with sulcus. This may be an interesting aspect for further research as gender specific outcomes after medialization thyroplasty for non-paralytic glottic incompetence has gained more attention recently, showing female having greater subjective improvement compared to male after surgery [12]. We would also consider to include this aspect in the pre-operative counselling of male patients by informing them that their voices may still be higher pitched after surgery.…”
Section: Discussionmentioning
confidence: 98%
“…In order to give comparison to other interventions’ effects on the VRQL, conventional speech therapy for presbyphonia patients was able to improve the total VRQL score by 4, 13 and type I thyroplasty improved male patients with glottic incompetence by 20.8. 14…”
Section: Discussionmentioning
confidence: 99%